Master of the Masquerade: An Atypical Presentation of Acute Aortic Dissection. (21st February 2020) - Mando, Ramy; Tim, Daniel; DeCicco, Anthony; Trivax, Justin; Hanson, Ivan
Abstract : Acute aortic dissection (AAD) is associated with unacceptably high mortality rate. As such, early diagnosis and aggressive management are essential in order to avoid life-threatening complications. Herein, we report an atypical presentation of AAD and clinical sequelae.